2013
DOI: 10.1021/jo402505f
|View full text |Cite
|
Sign up to set email alerts
|

Rh(I)-Catalyzed Transformation of Propargyl Vinyl Ethers into (E,Z)-Dienals: Stereoelectronic Role of trans Effect in a Metal-Mediated Pericyclic Process and a Shift from Homogeneous to Heterogeneous Catalysis During a One-Pot Reaction

Abstract: The combination of experiments and computations reveals unusual features of stereoselective Rh(I)-catalyzed transformation of propargyl vinyl ethers into (E,Z)-dienals. The first step, the conversion of propargyl vinyl ethers into allene aldehydes, proceeds under homogeneous conditions via a "cyclization-mediated" mechanism initiated by Rh(I) coordination at the alkyne. This path agrees well with the small experimental effects of substituents on the carbinol carbon. The key feature revealed by the computationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 136 publications
0
17
0
Order By: Relevance
“…This Rh(I)-catalyzed isomerization involves oxidative addition through TS′ D-E to give an unstable η 3 -allyl rhodium(III)-hydride intermediate E′ (Δ G = 0.7 kcal/mol). Such Rh(I)-mediated allylic C sp3 –H activation was also proposed to be involved in another Rh(I)-catalyzed cycloisomerization reactions 40,45,46 . Notably, this Rh(I)-catalyzed C sp3 –H activation (oxidative addition) process is different from the common pathway involving β-hydride elimination from rhoda(III)bicyclic intermediates (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This Rh(I)-catalyzed isomerization involves oxidative addition through TS′ D-E to give an unstable η 3 -allyl rhodium(III)-hydride intermediate E′ (Δ G = 0.7 kcal/mol). Such Rh(I)-mediated allylic C sp3 –H activation was also proposed to be involved in another Rh(I)-catalyzed cycloisomerization reactions 40,45,46 . Notably, this Rh(I)-catalyzed C sp3 –H activation (oxidative addition) process is different from the common pathway involving β-hydride elimination from rhoda(III)bicyclic intermediates (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 and Fig. 4) 40 , in which the two phosphine atoms of L4 and a PPh 3 ligand as well as the alkyne moiety of 1a coordinate to the acidic rhodium(I) metal. Then, the cationic metal complex APh preferentially undergoes 5- exo - dig cyclization with two new C-C bond formations to give a stable rhodium(I)-carbenoid complex BPh R (Δ G = –2.9 kcal/mol) with a barrier of about 22.4 kcal/mol in solution by the M06-L method.…”
Section: Resultsmentioning
confidence: 99%
“…Nucleophilic attack of the alkyne yields vinyl cation III , which is intercepted by water. The enol C can now either undergo keto–enol tautomerization or the 1,5‐H shift described by Vidhani et al.,14 directly forming dienone 6 a . A DFT‐based computational analysis at a M06‐2X/6‐31+G(d,p) level of theory (Figure 1) clearly demonstrates that the 1,5‐H shift (activation barrier: 13.6 kcal mol −1 ) is favored over the keto–enol tautomerization (activation barrier: 57.9 kcal mol −1 ).…”
Section: Methodsmentioning
confidence: 96%
“…Af urther well-investigated methodf or the synthesis of dienones is the Claisen rearrangemento fv inyl ethers. [10] Examples have been reported for this type of reaction utilizing Au, [11] Ag, [12] and Rh [13] catalysts, yieldings table pyransi nafew cases.Amechanistic analysis of aR h-catalyzed process, presented by Vidhani, Krafft,a nd Alabugin in 2014, [14] revealed that the transition metal catalystw as indeedo nly facilitating the Claisen rearrangement to allene-enol C (Scheme 2). C was then predicted to undergo spontaneous 1,5-hydride shift in the absence of the catalyst.…”
mentioning
confidence: 99%
“…2H), 0.92 (t, J = 7.3 Hz, 3H) 13 C NMR (151 MHz, CDCl3) δ 141.42, 128.66, 128.33, 126.76, 87.84, 80.02, 65.00, 30.77, 22.10, 18.63, 13.70. IR max (solid/cm -1 ) 3362 (O-H), 2957 (C-H), 2931 (C-H), 2871 (C-H), 1641, 1497, 1314, 999, 696.4-(1-Hydroxyhept-2-yn-1yl) Benzonitrile (7a)[4] …”
mentioning
confidence: 99%